Mekanisme Kepemimpinan Transformasional Dalam Sektor Publik - M. Furqon Wahyudi; Taufiq Harris; Muhammad Ainul Yaqin (Akademika, 2025)
The development of the digitalization world requires all leaders to provide changes, including changes in the public sector, this is characterized by all forms of changes or reports using digitalization. Research using the Literature study, to determine the mechanism of transformational leadership in the public sector. Research results In its implementation, the theory of leadership transformation of the public sector is also still a polemic and a dilemma. Because most of the bureaucratic systems in the public sector are still central and rigid with existing rules. However, in some countries that have implemented NPM, the transformational leadership approach in the public sector is very appropriate